Efetividade do clareamento caseiro e seus efeitos: uma revisão bibliográfica - Umeda, Jessica Mirella (2020)
The smile has never been as valued as today. Whiter teeth mean social status, success, hygiene, happiness and it is able to return self esteem and wellness to the patient. Thus tooth whitening is an aesthetic procedure that is very sought after in dental offices and it consists of applying gels based on carbamide peroxide and hydrogen peroxide. Among the recommended techniques, there are in-office whitening and home whitening. This present work aims to do a bibliographic survey of home bleaching, in between the years 2000 and 2019, in the Pubmed, Lilacs and Scielo Databases, to assess their effectiveness, advantages and disadvantages. The conclusion is: to minimize adverse effects that may arise such as sensitivity, cytotoxicity and gingival irritation, the minimum exposure time of the product is recommended; the technique of home bleaching demonstrates the best aesthetic results, when compared to the in-office whitening because it has a lower chance of recurrence after the treatment; requires research with a number of bigger experimental groups, obtaining formulations and different whitening gels concentrations.